La batalla de Madrid / López Muįz ; [con la] colaboración [de] Santiago Mateo Marcos y Juan Mateo Marcos - Mateo Marcos, SantiagoMateo Marcos, Juan; López Muįz, Gregorio (n. 1899)
Contiene ocho gráficos de las operaciones militarares de la Batalla de Madrid